Respiratory training in older women: Unravelling central and peripheral hemodynamic slow oscillatory patterns - Gabriel Dias Rodrigues; Antonio Claudio Lucas da Nobrega; Pedro Paulo da Silva Soares (Experimental Gerontology, 2023)
We hypothesized that inspiratory muscle training (IMT) increases the respiratory-induced low-frequency oscillations of mean blood pressure (MBP) and middle cerebral artery blood velocity (MCAv), upregulating cerebrovascular function in older women. Firstly, participants were recorded with free-breathing (FB) and then breathed at a slow-paced frequency (0.1 Hz; DB test) supported by sonorous metronome feedback. Blood pressure was recorded using finger photoplethysmography method, ECG, and respiration using a thoracic belt. To obtain the MCAv a transcranial ultrasound Doppler device was used. Spectral analysis of MBP, R-R intervals, and mean MCAv time series was obtained by an autoregressive model. The transfer function analysis (TFA) was employed to calculate the coherence, gain, and phase. After that, older women were enrolled in a randomized controlled protocol, the IMT-group (n = 8; 64 ± 3 years-old) performed IMT at 50 % of maximal inspiratory pressure (MIP), and Sham-group, a placebo training at 5 % MIP (Sham-group; n = 6; 66 ± 3 years-old). Participants breathed against an inspiratory resistance twice a day for 4-weeks. DB test is repeated post IMT and Sham interventions. IMT-group, compared to Sham-group, augmented tidal volume responses to DB (Sham-group 1.03 ± 0.41 vs. IMT-group 1.61 ± 0.56 L; p = 0.04), increased respiratory-induced MBP (Sham-group 26.37 ± 4.46 vs. IMT-group 48.21 ± 3.15 mmHg2; p = 0.04) and MCAv (Sham-group 14.16 ± 31.26 vs. IMT-group 79.90 ± 21.76 cm2s−2; p = 0.03) slow oscillations, and reduced TFA gain (Sham-group 2.46 ± 1.32 vs. IMT-group 1.78 ± 1.30 cm·s−1.mmHg−1; p = 0.01). Our findings suggest that IMT increases the respiratory-induced oscillations in MBP and MCAv signals and reduces TFA gain. It seems compatible with an improved dynamic cerebrovascular regulation following IMT in older women.